2015
DOI: 10.1038/srep11619
|View full text |Cite
|
Sign up to set email alerts
|

Competition-cooperation relationship networks characterize the competition and cooperation between proteins

Abstract: By analyzing protein-protein interaction (PPI) networks, one can find that a protein may have multiple binding partners. However, it is difficult to determine whether the interactions with these partners occur simultaneously from binary PPIs alone. Here, we construct the yeast and human competition-cooperation relationship networks (CCRNs) based on protein structural interactomes to clearly exhibit the relationship (competition or cooperation) between two partners of the same protein. If two partners compete f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Those results could be reproduced over a range of thresholds for binding site overlap definition ( Supplementary Figure S4 ). The reason could be that alternative regulatory mechanisms prevent competition between partners ( Li et al, 2015 ) or that our computational estimates of competition vs. cooperative binding are not accurate. For example, biophysical properties of interaction sites of proteins (e.g., steric hindrance) can favor or prevent interactions between them and thus, the classification of proteins based on the overlap in the interaction interface might not represent competitive or cooperative binding in reality.…”
Section: Discussionmentioning
confidence: 99%
“…Those results could be reproduced over a range of thresholds for binding site overlap definition ( Supplementary Figure S4 ). The reason could be that alternative regulatory mechanisms prevent competition between partners ( Li et al, 2015 ) or that our computational estimates of competition vs. cooperative binding are not accurate. For example, biophysical properties of interaction sites of proteins (e.g., steric hindrance) can favor or prevent interactions between them and thus, the classification of proteins based on the overlap in the interaction interface might not represent competitive or cooperative binding in reality.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that GO annotation, gene expression pattern, and subcellular localization information demonstrated the accuracy of PPI networks, there could still be false positives and false negatives in PPI networks. Proteins with higher degree or betweenness centrality play crucial roles in many cellular processes [ 32 , 33 ], thus given that in this study, the virulence factors showed higher degree and betweenness centrality, indicating their functional importance. Among 195 virulence factors, the degree of 28 ranked in the top 10% of degree distribution (hubs).…”
Section: Discussionmentioning
confidence: 73%
“…PPIs provide a systems understanding of protein functionality at the cellular level (Gu et al 2011;He et al 2010;Li et al 2015). To thoroughly understand the molecular mechanism of PPIs, the identification of protein interaction sites is a crucial step.…”
Section: Discussionmentioning
confidence: 99%